2013
DOI: 10.5194/acp-13-9057-2013
|View full text |Cite
|
Sign up to set email alerts
|

Key chemical NO<sub>x</sub> sink uncertainties and how they influence top-down emissions of nitrogen oxides

Abstract: Abstract. Triggered by recent developments from laboratory and field studies regarding major NOx sink pathways in the troposphere, this study evaluates the influence of chemical uncertainties in NOx sinks for global NOx distributions calculated by the IMAGESv2 chemistry-transport model, and quantifies their significance for top-down NOx emission estimates. Our study focuses on five key chemical parameters believed to be of primary importance, more specifically, the rate of the reaction of NO2 with OH radicals,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 105 publications
5
133
1
Order By: Relevance
“…in Stavrakou et al, 2013) in estimating satellite-born NO x emissions, which encourages the usage of the mass balance technique when one cannot employ modelling results that calculate an adjoint matrix as well.…”
Section: Top-down and A Posteriori Emissions Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…in Stavrakou et al, 2013) in estimating satellite-born NO x emissions, which encourages the usage of the mass balance technique when one cannot employ modelling results that calculate an adjoint matrix as well.…”
Section: Top-down and A Posteriori Emissions Estimatesmentioning
confidence: 99%
“…The obtained quantity is converted into a SO 2 VCD using an air mass factor, AMF, which accounts for changes in measurement sensitivity due to observation geometry, ozone column, clouds and surface reflectivity. The anthropogenic SO 2 profile required in the AMF calculation has been extracted from the Intermediate Model of the Global and Annual Evolution of Species, IMAGESv2, global tropospheric chemistry transport model (Stavrakou et al, 2013, and references therein) on a daily basis and for the overpass time of OMI. All details on the BIRA OMI SO 2 algorithm can be found in Theys et al (2015), updated recently in Theys et al (2017) in preparation for TROPOspheric Monitoring Instrument (TROPOMI) instrument.…”
Section: The Omi/aura So 2 Observationsmentioning
confidence: 99%
“…The SO 2 SCDs are converted to VCDs using AMFs from a look-up table, which is generated using the Linearized Discrete Ordinate Radiative Transfer (LIDORT) version 3.3 RTM (Spurr et al, 2001(Spurr et al, , 2008. SFs for SO 2 are obtained from the IMAGES CTM (Müller and Brasseur, 1995) for individual measurements at a horizontal resolution of 2 • × 2.5 • and at 40 vertical unevenly distributed levels extending from the surface to the lower stratosphere (44 hPa) (Stavrakou et al, 2013. Like for the OMSO2 data set, the cloud information is obtained from the OMCLDO2 cloud product.…”
Section: Max-doas Instrument and Data Analysismentioning
confidence: 99%
“…Global chemical data assimilation (e.g., Inness et al, 2015;Miyazaki et al, 2015) and emission inversion (e.g., Stavrakou et al, 2013;Miyazaki et al, 2017) would also benefit from high-resolution global CTMs through improvements in model performance (e.g., Arellano Jr. et al, 2007) and reduced spatial representation gaps between observed and simulated fields. Several previous studies (Mijling and van der A, 2012;Ding et al, 2017b;Liu et al, 2017) demonstrated the importance of high-resolution modeling in detecting small-scale NO x emission sources such as urban, new power plant, and ship emissions.…”
Section: Introductionmentioning
confidence: 99%